Transmission, Tropism, and Biological Impacts of Torix Rickettsia in the Common Bed Bug Cimex lectularius (Hemiptera: Cimicidae) - Thongprem, Panupong; Evison, Sophie E. F.; Hurst, Gregory D. D.; Otti, Oliver (Frontiers in Microbiology, 2020)
The torix group of Rickettsia have been recorded from a wide assemblage of invertebrates, but details of transmission and biological impacts on the host have rarely been established. The common bed bug (Cimex lectularius) is a hemipteran insect which lives as an obligatory hematophagous pest of humans and is host to a primary Wolbachia symbiont and two facultative symbionts, a BEV-like symbiont, and a torix group Rickettsia. In this study, we first note the presence of a single Rickettsia strain in multiple laboratory bed bug isolates derived from Europe and Africa. Importantly, we discovered that the Rickettsia has segregated in two laboratory strains, providing infected and uninfected isogenic lines for study. Crosses with these lines established transmission was purely maternal. Fluorescence in-situ hybridization analysis indicates Rickettsia infected in oocytes and bacteriomes, and other somatic tissues. We found no evidence that Rickettsia infection was associated with sex ratio distortion activity, but Rickettsia infected individuals developed from first instar to adult more slowly. The impact of Rickettsia on fecundity and fertility resulted in infected females producing fewer fertile eggs. However, we could not find any evidence for cytoplasmic incompatibility associated with Rickettsia presence. These data imply the existence of an unknown benefit to C. lectularius carrying Rickettsia that awaits further research.